Divergence time estimation of aloes and allies (Xanthorrhoeaceae) based on three marker genes - Khodaei, Zeinab; Van Wyk, Ben-Erik; Wink, Michael (Diversity, 2018)
Aloes and allies are prominent members of African succulent vegetation and especially of the highly diverse Cape Flora. The main goal of this study was to obtain age estimates for alooids by calibrating a Bayesian phylogenetic analysis based on two chloroplast markers (the trnL-trnF spacer region and rbcL gene) and one gene marker (ITS) using a relaxed molecular clock. Seventy four species from all succulent genera of alooids were analysed with MrBayes to infer species relationships. We discuss the age estimates to address the question whether vicariance or dispersal could account for the diversification of Madagascan alooids. In the combined maximum clade credibility tree obtained from BEAST the succulent alooids have split from asphodeloids around 51.8 Mya in Early Miocene. Divergence time age estimation for succulent drought resistant alooids (late Oligocene to early Miocene) correspond well with dates identified for several other plant lineages in southern Africa and does match with the start of dry period in Miocene which triggered speciation and evolutionary radiation of these genera and families. All climbing aloes and some tree aloes which were recently split into new genera are amongst the early diverged group in alooids and the crown node of this group diverged around 16.82 (15.5–22.4) Mya. The oldest node age estimation for aloes from Madagascar (5.1 Mya) is in early Pliocene and our findings support the hypothesis that the Africa-Madagascan divergence is best explained by oceanic long-distance dispersal rather than vicariance. This study is one of the first to give age estimates for clades of alooids in Xanthorrhoeaceae as a starting point for future studies on the historical biogeography of this family of succulent plants which are important for ethnomedicine, and as ornamental and horticultural plants.